Answer:
I'm going to lay this out in a chart so it's a little easier to see:
F(x) = f(g(x))
x | f (x) | f ' (x) | g (x) | g ' (x)
--------------------------------------
-2 | 8 | 4 |
5 | | 3 | -2 | 6
Remember the chain rule, which says
(f (g (x))) ' = g ' (x) f ' (g (x))
When they ask for F ' (5), they are asking for (f (g (x))) ' when x = 5.
Using the chain rule, that's
F ' (5) = g ' (5) f ' (g (5))
We can simplify using the numbers provided.
F ' (5) = (6) f ' (-2)
F ' (5) = (6) (4)
F ' (5) = 24
I hope that helps!
by jannat <33
Answer:
Hi...u should do like this
18>3f>4
6>f>4/3
The answer would be D, as it is the closest option.
Answer:
the function is only increasing.
Step-by-step explanation: